Jovens atores da gestão: Origens de classe, percursos profissionais e competências - Amândio, S. (Tese de Doutoramento em Sociologia, ISCTE-IUL, Lisboa, 2014)
This thesis aims to understand young Portuguese managers - graduated between 1994 and 2010 - from the stand point of B. Lahire’s sociology of socialization. Since the 1990s, and especially since 2000, management subject’s occupy a crucial place in the study of the Portuguese modern society: (1) expansion of management higher education, (2) statistical growth of the group of ‘business and administration professionals’, (3) internationalization of the cycles of thought of Northern American management, (4) international spreading of the argument of managerialism, (5) constitution of the critical management studies (CMS). It is proposed a genealogy of transmission and incorporation of professional competences, treading a line of counterintuitive research on the social world of management and managers who are reluctant to (plural) management socialization. The implementation of a model on the resistance to management socialization aimed at revealing relevant social realities.